Invasive Zygomycosis: Epidemiology and Clinical Features (Review) - NS Bagirova (Клиническая онкогематология)
The invasive zygomycosis is the third most common mycosis following invasive candidiasis and aspergillosis. Patients with hematological malignancies and patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT) are two main risk groups for the disease. In addition, zygomycosis is important for patients with diabetes. The review presents detailed description of epidemiology, risk factors, clinical types of zygomycosis, and features of therapy.